The use of Teaching Competencies during the period 1990-2019 from the point of view of a bibliometric meta-analysis - Lorenzo-Lledó, Gonzalo; Orellana-Lepe, Gladys Andrea; Lledó-Carreres, Asunción (Revista General de Información y Documentación, 2021)
point of view of a bibliometric meta-analysis. Abstract. Nowadays societies, education is a crucial element in social and economic development. More specifically, with the creation of the European Higher Education Area, it acquires a central position as an element that unities society and the working environment, leading to the skills learning model. As a consequence, a systematic and thematic review of scientific production in teaching skills during the period 1990-2019 in the Scopus and WOS databases is proposed as the objective of the research. The sample consists of 1704 documents. Results show that WS has the highest production period in 2015-2018 while Scopus is 2016-2019. Similarly, Scopus allows you to get quote for articles much faster than WOS. The field of work has a great international dissemination since the most producing countries must spread their knowledge. On the other hand, the work teams are usually between 2 and 3 authors demonstrating that it is a growing field and finally there is no nigh diffusion in high quartile journals due to the high overlapping percentages. As future lines of work it is proposed to use Bibliometrix or Vosviewer computer software to study other bibliometric indicators such as word co-occurrence or trending topic within the field.